Dietary fibre alleviates hepatic fat deposition via inhibiting lipogenic gene expression in meat ducks. Issue 2 (3rd November 2017) - Qin, S.; Han, H.; Zhang, K.; Ding, X.; Bai, S.; Wang, J.; Zeng, Q.
Summary: This study investigated the effect of dietary fibre (DF) supplementation on hepatic fat deposition of Cherry Valley meat ducks. A total of 600 1‐d‐old ducks were randomly allotted to five dietary fibre diets (1.46 (basal diet), 3.09, 4.15, 6.18 and 7.52% (analysed)) for 14 days. Growth performance decreased with increasing DF concentrations, when the DF level more than 6.18% the average daily gain (ADG) and feed conversion ratio (F/G) markedly decreased in meat ducks. Meat ducks supplemented over 4.15% DF had lower percentage of liver reported to live weight, liver lipid contents, hepatic triglyceride and total cholesterol concentrations as well as decreased serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) concentrations at 14 days. The transcription of fatty acid synthase (FAS), acetyl‐CoA carboxylase (ACC) and sterol‐regulatory element‐binding protein‐1 (SREBP‐1) in liver was significantly reduced by DF, while no any significant difference was found about the effect of DF on hepatic peroxisome proliferator‐activated receptor α (PPARα), adipose triglyceride lipase (ATGL), transcription as well as caecal digesta short‐chain fatty acids (SCFA). Data suggested that dietary fibre supplementation decreased hepatic lipid deposition and improved characteristics of liver health via inhibiting hepatic FAS, ACC and SREBP‐1 expression in meat ducks.